2012
DOI: 10.2118/142854-pa
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Well-Integrity Risk: A Qualitative Model

Abstract: For successful delivery of well integrity (WI), there needs to be an understanding of the risks that can cause undesirable events such as safety hazards or loss of containment. Performing a risk assessment (RA) on a well, or type of well, will help determine and rank the potential risks and provide information that allows limited resources to be applied in the most effective manner. The main objectives of performing a risk assessment include (a) following a formal process to assess risk consistently and to ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Thus, they considered blowout and well control to have the same degree of risk. Poedjono et al (2009) and Dethlefs and Chastain (2012) also documented the use of RMs in a drilling context, but they used the more common practice of multiplying the probability and consequence scores to obtain a "risk score" for each outcome. Table 2 shows the results of applying this procedure to the Pritchard et al (2010) example.…”
Section: Rmsmentioning
confidence: 99%
“…Thus, they considered blowout and well control to have the same degree of risk. Poedjono et al (2009) and Dethlefs and Chastain (2012) also documented the use of RMs in a drilling context, but they used the more common practice of multiplying the probability and consequence scores to obtain a "risk score" for each outcome. Table 2 shows the results of applying this procedure to the Pritchard et al (2010) example.…”
Section: Rmsmentioning
confidence: 99%
“…Risk matrices are easy to implement and can be implemented even where data are limited. Therefore, they have become popular decision-support tools in both the public and private sectors, (3)(4)(5)(6) in areas such as well-integrity risk, (7) drilling hazard management, (8) climatic change responses, (9) and so on. However, despite its simplicity and wide usage, recent research has revealed several flaws in the risk matrix.…”
Section: Introductionmentioning
confidence: 99%
“…(16) However, when risk matrices are used to prioritize several risks, risk matrices should have a higher resolution to better differentiate all the risks. (3,7,8,15,19) As a result, when we design the rating scheme of a risk matrix, the method we use should work as well as possible regardless of the various inclinations for resolution.…”
Section: Introductionmentioning
confidence: 99%
“…They cited several reasons for GLV failures, including flow cutting in sealing seats caused by well unloading of completion fluids, the valve-spring fatigue failure, damage during installation, erosion during multiphase or wet gas injection, and damage to valve seat caused by chattering in a low-pressure-drop situation. Gilbertson et al (2013) developed a thermally actuated GLV for offshore wells to add redundancy to well systems and significantly to increase well safety. This valve avoids the use of either active control or passive pressure-induced actuation that is performed in current valve systems.…”
Section: Introductionmentioning
confidence: 99%